2021
DOI: 10.1186/s12903-021-01752-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical efficacy of mineralized collagen (MC) versus anorganic bovine bone (Bio-Oss) for immediate implant placement in esthetic area: a single-center retrospective study

Abstract: Background The purpose of this retrospective study was to evaluate the clinical efficacy of mineralized collagen (MC) versus anorganic bovine bone (Bio-Oss) for immediate implant placement in esthetic area. Methods Medical records of Department of Oral and Maxillofacial Surgery of Shandong Provincial Hospital were screened for patients who had been treated with immediate implant implantation in the esthetic area using either MC (Allgens®, Beijing A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…DIPY, an indirect adenosine agonist, is an extensively studied biologic compound [ 55 , 62 , 63 , 64 , 65 , 65 , 66 , 67 , 67 , 68 , 68 , 69 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. Historically, it has been used as a vasodilatory and antiplatelet agent [ 98 , 99 , 100 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…DIPY, an indirect adenosine agonist, is an extensively studied biologic compound [ 55 , 62 , 63 , 64 , 65 , 65 , 66 , 67 , 67 , 68 , 68 , 69 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 ]. Historically, it has been used as a vasodilatory and antiplatelet agent [ 98 , 99 , 100 , 101 ].…”
Section: Resultsmentioning
confidence: 99%
“…3.3.1. DIPY DIPY, an indirect adenosine agonist, is an extensively studied biologic compound [55,[62][63][64][65][65][66][67]67,68,68,69,[81][82][83][84][85][86][87][88][89][90][91][92][93][94][95][96][97]. Historically, it has been used as a vasodilatory and antiplatelet agent [98][99][100][101].…”
Section: Indirect Agonistsmentioning
confidence: 99%
“…The alveolar process contracts to a certain extent due to the reduction of the biomechanical stimulation and the physiological remodeling of the alveolar bone to fill the postextraction space. Some studies showed that bone remodeling results in 40–60% of the vertical and horizontal bone loss during the first two years of alveolar bone healing. , Bio-Oss is widely used in clinical practice for the preservation of the alveolar ridge, achieving good results to some extent. However, it is prone to collapse, and it does not maintain a good and stable shape . Hence, the ideal material for alveolar bone healing has not yet been found.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is prone to collapse, and it does not maintain a good and stable shape. 7 Hence, the ideal material for alveolar bone healing has not yet been found.…”
Section: Introductionmentioning
confidence: 99%
“…ICBM mainly consists of collagen type I [ 7 ], whereas BioOss ® Collagen consists of a mixture of cancellous granules and collagen [ 8 ]. ICBM is predominately used in research settings [ 6 , 7 ], BioOss ® is often used in clinical routines [ 9 , 10 ]. Augmentative results of xenogeneic materials vary in literature [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%